Preparation method of slow-rebound soft material

Through the design of polyurethane material with internal and external double-layer configurations, the problem of slow rebound polyurethane material hardening at low temperatures is solved, and the cost is reduced by reducing the amount of antibacterial components, achieving the softness and antibacterial properties of the material. Improvement, suitable for the production of pressure-reducing toys.

CN117962449BActive Publication Date: 2024-12-20ZHEJIANG MOLIN ARTS & CRAFTS CO LTD
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
CN202410198919.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-02-22
Publication Date
2024-12-20
Estimated Expiration
2044-02-22

AI Technical Summary

Technical Problem

The existing slow rebound polyurethane materials have a high hardening range at low temperatures, and the addition of a larger proportion of antibacterial components leads to high costs and needs to be improved.

Method used

The preparation method of slow rebound soft material with double-layer internal and external configurations is adopted. The inner polyurethane-layer one increases flexibility by adding high cis-terminal hydroxy polybutadiene and end hydroxy polydimethylsiloxane, while the outer polyurethane-layer two increases end Hydroxydimethylsiloxane quaternary ammonium salt and titanium dioxide composite particles to improve antibacterial properties and reduce the amount of antibacterial components.

Benefits of technology

It extends the elastic recovery time, improves the softness of the material at low temperatures, significantly improves the antibacterial effect, reduces costs, and is suitable for the production of decompression toys.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004710704940000051
    Figure BDA0004710704940000051
  • Figure HDA0004710704950000011
    Figure HDA0004710704950000011
Patent Text Reader

Abstract

The invention discloses a preparation method of a slow-rebound soft material. In the scheme, the slow-rebound soft material adopts an inner and outer double-layer configuration, wherein the inner layer is formed by polyurethane one, the synthetic components of polyurethane one are designed, and high cis-terminal hydroxyl polybutadiene and terminal hydroxyl polydimethylsiloxane are added to improve the flexibility of the material; the outer layer is formed by mixing polyurethane two with other components, and the components of polyurethane two are designed. In comparison, terminal hydroxyl polydimethylsiloxane quaternary ammonium salt is added to improve the antibacterial type, and titanium dioxide composite particles are introduced in the outer layer molding. The antibacterial property of the material is improved under coordination, and the inner and outer double-layer configuration helps to reduce the amount of antibacterial components added, which helps to reduce costs.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of materials, and in particular to a method for preparing a slow-rebound soft material. Background Art

[0002] Slow-rebound polyurethane materials are widely used in furniture, toys, automotive accessories, sports equipment, medical equipment and other fields due to their shape memory, energy absorption, sound absorption and shock absorption functions. Taking toys as an example, decompression toys made of slow-rebound polyurethane materials, such as spheres, are currently widely welcomed. The decompression toys made of slow-rebound polyurethane materials on the market have defects such as a large degree of hardening at low temperatures. Generally, a large proportion of antibacterial components are added to make the toys have better antibacterial properties. The large amount leads to high costs and needs to be improved. Summary of the invention

[0003] To solve at least one of the above technical defects, the present invention provides the following technical solutions:

[0004] This application document discloses a method for preparing a slow-rebound soft material, comprising the following steps:

[0005] First, the preparation of polyurethane 1, polyether polyol 1 with a hydroxyl value of 200-250 mgKOH / g, polyether polyol 2 with a hydroxyl value of 52-58 mgKOH / g, polypropylene glycol, high cis-terminated hydroxyl polybutadiene, isophorone diisocyanate, hydroxyl-terminated polydimethylsiloxane, a foaming agent, a pore opening agent, a catalyst, and water are mixed to prepare polyurethane 1;

[0006] Second, preparation of polyurethane II, polyether polyol I with a hydroxyl value of 200-250 mgKOH / g, polyether polyol II with a hydroxyl value of 52-58 mgKOH / g, polypropylene glycol, high cis-terminated hydroxyl polybutadiene, isophorone diisocyanate, hydroxyl-terminated polydimethylsiloxane quaternary ammonium salt, foam leveling agent, pore opening agent, catalyst and water are mixed to prepare polyurethane II;

[0007] Third, forming, forming an inner layer with polyurethane 1, and coating the inner layer with a mixture of polyurethane 2, antioxidant, lubricant, titanium dioxide composite particles, and coupling agent to form an outer layer.

[0008] In this scheme, the slow-rebound soft material adopts an inner and outer double-layer configuration, wherein the inner layer is formed by polyurethane one, and the synthetic components of polyurethane one are designed, and high cis-terminal hydroxyl polybutadiene and terminal hydroxyl polydimethylsiloxane are added to improve the flexibility of the material; the outer layer is formed by mixing polyurethane two with other components, and the components of polyurethane two are designed. In comparison, terminal hydroxyl polydimethylsiloxane quaternary ammonium salt is added to improve the antibacterial type, and titanium dioxide composite particles are introduced in the outer layer molding. The antibacterial property of the material is improved under the coordination, and the inner and outer double-layer configuration helps to reduce the amount of antibacterial components added, which helps to reduce costs.

[0009] Furthermore, in the preparation of polyurethane one, the proportion of each component by mass is as follows: 60-70 parts of polyether polyol one with a hydroxyl value of 200-250 mgKOH / g, 20-30 parts of polyether polyol two with a hydroxyl value of 52-58 mgKOH / g, 1-2 parts of polypropylene glycol, 3-5 parts of high cis-terminated hydroxyl polybutadiene, 40-50 parts of isophorone diisocyanate, 4-7 parts of terminal hydroxyl polydimethylsiloxane, 0.5-0.8 parts of foaming agent, 0.1-0.3 parts of pore opening agent, 1-2.5 parts of catalyst, and 1-2 parts of water. The type and proportion of polyether polyol one and polyether polyol are designed. Under this component proportion, the elastic recovery time of the material is increased, and the material is more flexible and more resistant to low temperatures.

[0010] Further, in the preparation of polyurethane II, the proportion of each component by mass is as follows: 60-70 parts of polyether polyol I with a hydroxyl value of 200-250 mgKOH / g, 20-30 parts of polyether polyol II with a hydroxyl value of 52-58 mgKOH / g, 1-2 parts of polypropylene glycol, 6-9 parts of high cis-terminated hydroxyl polybutadiene, 40-50 parts of isophorone diisocyanate, 1-2 parts of hydroxyl-terminated polydimethylsiloxane quaternary ammonium salt, 0.5-0.8 parts of a foam leveling agent, 0.1-0.3 parts of a pore opener, 1-2.5 parts of a catalyst, and 1-2 parts of water are mixed and reacted to prepare polyurethane II;

[0011] 70-80 parts of polyurethane II, 0.7-1.2 parts of antioxidant, 1-2 parts of lubricant, 0.6-0.9 parts of titanium dioxide composite particles, and 0.3-1 parts of coupling agent are mixed. The proportion of the components of polyurethane II is fine-tuned in the terminal hydroxyl polydimethylsiloxane quaternary ammonium salt and high cis terminal hydroxyl polybutadiene, so that the material can maintain flexibility at low temperatures and have antibacterial properties. Under the action of the coupling agent, it helps to improve the stability of the connection between titanium dioxide and the polyurethane components.

[0012] Furthermore, the titanium dioxide composite lubricant II is prepared as follows: adding nano titanium dioxide to a 2-5% stearic acid cyclohexane solution, heating for reaction and condensing and refluxing, solid-liquid separation and pulverization to obtain the titanium dioxide composite lubricant II, and then modifying it.

[0013] Furthermore, the catalyst is a composite type, comprising triethylenediamine and dibutyltin dilaurate, the mass ratio of which is 1::0.2-0.5, and is combined with a foam leveling agent and a pore opening agent to reduce the hardness of the molding material, increase the softness of the material, and improve the hand feel.

[0014] Compared with the prior art, the present invention has the following beneficial effects:

[0015] 1. The slow-rebound soft material prepared by the present invention prolongs the elastic recovery time, improves the softness of the material at low temperatures, and has an outstanding antibacterial effect, and is suitable for application in the production of decompression toys and the like. BRIEF DESCRIPTION OF THE DRAWINGS

[0016] In order to more clearly illustrate the technical solutions in the embodiments of the present invention, the following briefly introduces the drawings required for use in the description of the embodiments. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.

[0017] Figure 1 It is the general structural formula of the quaternary ammonium salt of terminal hydroxyl polydimethylsiloxane; DETAILED DESCRIPTION

[0018] The present invention will be further described below in conjunction with the accompanying drawings and specific embodiments.

[0019] The structural formula of the hydroxy-terminated polydimethylsiloxane quaternary ammonium salt is as described in the patent document with application number 2019102012824. Figure 1 As shown, it can be directly purchased from the market or synthesized using the synthetic route described in Example 1, as follows:

[0020] In a single-necked flask equipped with a spherical condenser and a magnet, 5.32 g of chloropropylmethyldiethoxysilane, 3.86 g of N,N-dimethyloctylamine and 7.5 ml of ethanol were added in sequence, stirred to mix evenly, protected by nitrogen, refluxed at 80°C, and reacted for 48 hours. After the reaction, low-boiling substances were removed by reduced pressure distillation to obtain a yellow transparent oily liquid. The product was washed three times with petroleum ether and vacuum dried for 24 hours to obtain methyldiethoxysilane quaternary ammonium salt monomer.

[0021] In a three-necked flask equipped with a spherical condenser, a thermometer, and a stirrer, 3.12 g of methyldiethoxysilane quaternary ammonium salt monomer, 30.15 g of terminal hydroxyl polydimethylsiloxane (number average molecular weight Mn=5800) and 0.34 g of tetramethylammonium hydroxide silicon alkoxide were added in sequence, stirred to make them evenly mixed, nitrogen protection, slowly heated to 70°C and maintained for 35 min, then heated to 100°C, reacted for 10 h, the system was heated to 130°C and maintained for 30 min, and then low-boiling substances were removed by vacuum distillation to obtain a light yellow transparent oily liquid, which was terminal hydroxyl polydimethylsiloxane quaternary ammonium salt. The obtained product was confirmed by nuclear magnetic resonance to be the same as Figure 1 The general structure corresponds to the Chinese one.

[0022] The preparation of titanium dioxide composite particles is as follows: add rutile nano-titanium dioxide (20-40nm) purchased from the market to a cyclohexane solution containing 4% stearic acid, the mass ratio of cyclohexane solution to nano-titanium dioxide is 200:1, heat to 80°C and maintain for 5 hours, during which time it is continuously stirred and condensed and refluxed, then the solid and liquid are separated by centrifugation, the obtained fraction is washed several times, and then vacuum dried at 30°C to obtain titanium dioxide composite particles. Infrared spectroscopy confirms the presence of long carbon chains on the titanium dioxide particles, namely stearic acid.

[0023] The catalyst is a composite type, and the catalyst includes triethylenediamine and dibutyltin dilaurate, and the mass ratio of the two is 1:0.3.

[0024] Polyether polyol 1 uses GLR-2000, with a hydroxyl value of 230-250 mgKOH / g, polyether polyol 2 uses 3010, with a hydroxyl value of 54-56 mgKOH / g, polypropylene glycol M n 1000, high cis-terminated hydroxyl polybutadiene M n 2000, terminal hydroxyl polydimethylsiloxane M n The molecular weight of the raw material is 2000, the foaming agent is L580, the cell opening agent is 1900, the antioxidant is 1010 and 168 in a mass ratio of 1:1, the lubricant is polyethylene wax, the coupling agent is KH550, and the water is deionized water.

[0025] Example 1

[0026] The preparation method of the slow-rebound soft material comprises the following steps:

[0027] First, the preparation of polyurethane 1 is as follows: by mass, 62 parts of polyether polyol 1, 22 parts of polyether polyol 2, 1.2 parts of polypropylene glycol, 3.2 parts of high cis-terminated hydroxyl polybutadiene, 4.1 parts of terminal hydroxyl polydimethylsiloxane, 0.6 parts of foaming agent, 0.1 parts of pore opening agent, 1.4 parts of catalyst and 1 part of water are added into a container and mixed evenly; the temperature is 26°C; then 43 parts of isophorone diisocyanate is added; after stirring for 10 seconds, the mixture is prepared according to the conventional reaction process.

[0028] Second, for the preparation of polyurethane II, 62 parts of polyether polyol I, 22 parts of polyether polyol II, 1.2 parts of polypropylene glycol, 6.5 parts of high cis-terminated hydroxyl polybutadiene, 1.5 parts of hydroxyl-terminated polydimethylsiloxane quaternary ammonium salt, 0.6 parts of foaming agent, 0.1 parts of pore opening agent, 1.4 parts of catalyst and 1 part of water were added into a container and mixed evenly. Then, 43 parts of isophorone diisocyanate was added into the container at 26°C, stirred for 10 seconds and then prepared according to the conventional reaction process.

[0029] Third, molding, adding the prepared polyurethane material into the mold, the mold temperature is 47±1℃, demolding after 100s to form an inner layer, the inner layer formed with polyurethane one is pre-placed in the prepared mold, the mold temperature is 47±1℃, 74 parts of polyurethane II, 0.7 parts of antioxidant, 1.3 parts of lubricant, 0.7 parts of titanium dioxide composite particles, and 0.4 parts of coupling agent are mixed and stirred evenly, then injected into the mold to form a coating on the inner layer, and demolding can be done after 2h. The product is a sphere with a mass ratio of inner layer to outer layer of 4:1.

[0030] Example 2

[0031] Compared with Example 1, the main difference in the preparation method of the slow-rebound soft material in this example is the component ratio:

[0032] First, in the preparation of polyurethane one, by mass, 65 parts of polyether polyol one, 25 parts of polyether polyol two, 1.6 parts of polypropylene glycol, 4.2 parts of high cis-terminated hydroxyl polybutadiene, 4.9 parts of terminal hydroxyl polydimethylsiloxane, 0.7 parts of foaming agent, 0.2 parts of pore opening agent, 1.4 parts of catalyst, 1 part of water, and 46 parts of isophorone diisocyanate are added.

[0033] Second, in the preparation of polyurethane II, by mass, 62 parts of polyether polyol I, 22 parts of polyether polyol II, 1.2 parts of polypropylene glycol, 7.6 parts of high cis-terminated hydroxyl polybutadiene, 1.6 parts of hydroxyl-terminated polydimethylsiloxane quaternary ammonium salt, 0.7 parts of foaming agent, 0.2 parts of pore opener, 1.4 parts of catalyst, 1 part of water, and 46 parts of isophorone diisocyanate.

[0034] Third, molding: 76 parts of polyurethane, 1 part of antioxidant, 1.6 parts of lubricant, 0.8 parts of titanium dioxide composite particles, and 0.4 parts of coupling agent.

[0035] Example 3

[0036] Compared with Example 1, the main difference in the preparation method of the slow-rebound soft material in this example is the component ratio:

[0037] First, in the preparation of polyurethane one, by mass, 70 parts of polyether polyol one, 27 parts of polyether polyol two, 1.8 parts of polypropylene glycol, 4.8 parts of high cis-terminated hydroxyl polybutadiene, 5.2 parts of terminal hydroxyl polydimethylsiloxane, 0.7 parts of foaming agent, 0.2 parts of pore opening agent, 1.6 parts of catalyst, 1.2 parts of water, and 48 parts of isophorone diisocyanate were added.

[0038] Second, in the preparation of polyurethane II, by mass, 70 parts of polyether polyol I, 27 parts of polyether polyol II, 1.8 parts of polypropylene glycol, 8.2 parts of high cis-terminated hydroxyl polybutadiene, 1.8 parts of hydroxyl-terminated polydimethylsiloxane quaternary ammonium salt, 0.8 parts of foaming agent, 0.2 parts of pore opening agent, 1.4 parts of catalyst, 1 part of water, and 48 parts of isophorone diisocyanate.

[0039] Third, molding: 78 parts of polyurethane, 1.1 parts of antioxidant, 1.8 parts of lubricant, 0.9 parts of titanium dioxide composite particles, and 0.6 parts of coupling agent.

[0040] Comparative Example 1

[0041] Compared with Example 1, the main differences of the preparation method of the slow-rebound soft material in this example are:

[0042] The terminal hydroxyl polydimethylsiloxane and the quaternary ammonium salt are added independently in the mass of the terminal hydroxyl polydimethylsiloxane quaternary ammonium salt contained in the terminal hydroxyl polydimethylsiloxane quaternary ammonium salt in Example 1.

[0043] Comparative Example 2

[0044] Compared with Example 1, the main differences of the preparation method of the slow-rebound soft material in this example are:

[0045] Titanium dioxide and stearic acid in an amount equivalent to that contained in the titanium dioxide composite particles in Example 1 were added separately.

[0046] The performance of the prepared products was tested, as shown in Table 1:

[0047] Table 1

[0048]

[0049] The spheres prepared in the above case are mainly used for hand-pinching to relieve pressure. According to feedback, the product is softer and hardens less at low temperatures such as in winter. It is speculated that with the combination of soft segments such as terminal hydroxyl polydimethylsiloxane and high cis-terminal hydroxyl polybutadiene, the glass transition temperature of the resulting polyurethane is lowered and its flexibility is improved.

[0050] According to Table 1, the spheres prepared in Examples 1-3 have excellent antibacterial properties, while the antibacterial properties of the spheres obtained by adding components such as quaternary ammonium salts independently are significantly reduced. According to detection, in the outer layer of the second-molded polyurethane of Examples 1-3, the quaternary ammonium salts combined with siloxane are mostly gathered on the surface, and the titanium dioxide compounded with stearic acid also has a more obvious surface migration characteristic. The two antibacterial components are gathered on the surface to cooperate with each other in antibacterial, and the amount of the antibacterial components is significantly reduced, while the surface aggregation phenomenon of the antibacterial components in Comparative Examples 1-2 is greatly reduced, and the antibacterial performance is significantly reduced.

[0051] The above are only preferred embodiments of the present invention. The protection scope of the present invention is not limited to the above embodiments. All technical solutions under the concept of the present invention belong to the protection scope of the present invention. It should be pointed out that for ordinary technicians in this technical field, some improvements and modifications without departing from the principle of the present invention should also be regarded as the protection scope of the present invention.

Claims

1. A method for preparing a slow-rebound soft material, characterized in that: The following steps are involved: First, the preparation of polyurethane 1, polyether polyol 1 with a hydroxyl value of 200-250 mgKOH / g, polyether polyol 2 with a hydroxyl value of 52-58 mgKOH / g, polypropylene glycol, high cis-terminated hydroxyl polybutadiene, isophorone diisocyanate, hydroxyl-terminated polydimethylsiloxane, a foaming agent, a pore opening agent, a catalyst, and water are mixed to prepare polyurethane 1; Second, preparation of polyurethane II, polyether polyol I with a hydroxyl value of 200-250 mgKOH / g, polyether polyol II with a hydroxyl value of 52-58 mgKOH / g, polypropylene glycol, high cis-terminated hydroxyl polybutadiene, isophorone diisocyanate, hydroxyl-terminated polydimethylsiloxane quaternary ammonium salt, foam leveling agent, pore opening agent, catalyst and water are mixed to prepare polyurethane II; Third, forming, forming an inner layer with polyurethane 1, and coating the inner layer with a mixture of polyurethane 2, antioxidant, lubricant, titanium dioxide composite particles, and coupling agent to form an outer layer; In the preparation of polyurethane 1, the proportion of each component by mass is as follows: 60-70 parts of polyether polyol 1 with a hydroxyl value of 200-250 mgKOH / g, 20-30 parts of polyether polyol 2 with a hydroxyl value of 52-58 mgKOH / g, 1-2 parts of polypropylene glycol, 3-5 parts of high cis-terminated hydroxyl polybutadiene, 40-50 parts of isophorone diisocyanate, 4-7 parts of hydroxyl-terminated polydimethylsiloxane, 0.5-0.8 parts of foam leveling agent, 0.1-0.3 parts of pore opening agent, 1-2.5 parts of catalyst, and 1-2 parts of water; In the preparation of polyurethane II, the proportion of each component by mass is as follows: 60-70 parts of polyether polyol I with a hydroxyl value of 200-250 mgKOH / g, 20-30 parts of polyether polyol II with a hydroxyl value of 52-58 mgKOH / g, 1-2 parts of polypropylene glycol, 6-9 parts of high cis-terminated hydroxyl polybutadiene, 40-50 parts of isophorone diisocyanate, 1-2 parts of hydroxyl-terminated polydimethylsiloxane quaternary ammonium salt, 0.5-0.8 parts of foam leveling agent, 0.1-0.3 parts of pore opening agent, 1-2.5 parts of catalyst and 1-2 parts of water are mixed and reacted to prepare polyurethane II; Mix 70-80 parts of polyurethane, 0.7-1.2 parts of antioxidant, 1-2 parts of lubricant, 0.6-0.9 parts of titanium dioxide composite particles, and 0.3-1 parts of coupling agent; The titanium dioxide composite particles are prepared as follows: adding nano titanium dioxide to a 2-5% stearic acid cyclohexane solution, heating for reaction and condensing and refluxing, and solid-liquid separation and pulverization to obtain titanium dioxide composite particles; The synthetic route of hydroxy-terminated polydimethylsiloxane quaternary ammonium salt is as follows: In a single-necked flask equipped with a spherical condenser and a magnet, 5.32 g of chloropropylmethyldiethoxysilane, 3.86 g of N,N-dimethyl-n-octylamine and 7.5 ml of ethanol were added in sequence, stirred to make them uniformly mixed, protected by nitrogen, refluxed at 80°C, and reacted for 48 hours. After the reaction was completed, low-boiling substances were removed by vacuum distillation to obtain a yellow transparent oily liquid. The product was washed three times with petroleum ether and vacuum dried for 24 hours to obtain methyldiethoxysilane quaternary ammonium salt monomer; In a three-necked flask equipped with a spherical condenser, a thermometer and a stirrer, 3.12g of methyldiethoxysilane quaternary ammonium salt monomer, 30.15g of terminal hydroxyl polydimethylsiloxane with a number average molecular weight of Mn=5800 and 0.34g of tetramethylammonium hydroxide silicon alkoxide were added in sequence, and stirred to mix evenly. Under nitrogen protection, the temperature was slowly raised to 70°C and maintained for 35min, then raised to 100°C and reacted for 10h. The system was heated to 130°C and maintained for 30min, and then low-boiling substances were removed by reduced pressure distillation to obtain a light yellow transparent oily liquid, which was terminal hydroxyl polydimethylsiloxane quaternary ammonium salt.

2. The method for preparing the slow-rebound soft material according to claim 1, characterized in that: The catalyst is a composite type, and the catalyst includes triethylenediamine and dibutyltin dilaurate, and the mass ratio of the two is 1:0.2-0.5.

Citation Information

Patent Citations

  • Polyurethane memory foam with superior anti-yellowing performance

    CN102391457A

  • Preparation method for nano-antibacterial coating

    CN105925174A

  • Preparation method of slow recovery sponge material

    CN106750176A

  • Quaternary ammonium salt-containing functionalized polysiloxane and synthesizing method thereof

    CN109912801A

  • Organosilicon quaternary ammonium salt modified polyurethane as well as preparation method and application thereof

    CN112679689A